Pengembangan Media Pembelajaran Berbasis Android Untuk Penumbuhan Literasi Sains Siswa Pada Materi Sistem Periodik Unsur - Ria Kusumawardhani; Suryati Suryati; Yusran Khery (Hydrogen: Jurnal Kependidikan Kimia, 2019)
The aims of this study were to produce android base learning media inelements periodic system subject material and to evaluate its eligibility,pratical, and effectiveness to grow student science litaracy. In form ofResearch and Development, this study was carried out by ADDIE Model(Analysis, Design, Development, Implementation and evaluation). Data wascollected by respons questionnaire, validaty questionnaire and scienceliteracy test. Data was analyzed by eligiblepercentage, eligiblecategorization, and N-gain test. Study result showed that content validity andmedia design validity was very eleigible with 81.11% and 83.97% ofeligibility respectively. Practicioner and student respon was very eligible with80.95 % and 89.02 % of eligibility respectively. Effectivity trial obtained 0.62of N-gain with moderate category. It can be concluded that android baselearning media was very eligible to applied for students science literacygrowth on elements periodic system learning effectively.